Japanese packaging design: An approach through ideogram language - Mercaldi, Marlon [UNESP]; Barcellos, Ekaterina Emmanuil Inglesis [UNESP]; Paschoarelli, Luiz Carlos [UNESP]; Botura, Galdenoro [UNESP] (Springer Nature, 2017)
This article aims to demonstrate the relationship between language and thought in the eastern culture. Given this relationship, it should examine how ideogrammatic writing influences the visual identity of Japanese packaging. The objective of this research is to identify the relationship between ideographic writing and the visual identity of Japanese packaging. It also try to determine at which level and aspect, the ideogrammatic language affects favorably or prejudice the design and the visual identity of the packaging of a product. This characteristic includes concepts of emotional and affective design and the messages they can transfer to the users. Established this association, it should consider how the diagrammatic writing influences the visual identity of the Japanese packaging.
Keywords: Ideogram; Packaging; Semiotics; Visual language